Brain morphology in children with nevoid basal cell carcinoma syndrome. Issue 4 (22nd March 2017) - Shiohama, Tadashi; Fujii, Katsunori; Miyashita, Toshiyuki; Mizuochi, Hiromi; Uchikawa, Hideki; Shimojo, Naoki
Abstract : Brain morphology is tightly regulated by diverse signaling pathways. Hedgehog signaling is a candidate pathway considered responsible for regulating brain morphology. Nevoid basal cell carcinoma syndrome (NBCCS), caused by a PTCH1 mutation in the hedgehog signaling pathway, occasionally exhibits macrocephaly and medulloblastoma. Although cerebellar enlargement occurs in ptch1 heterozygous‐deficient mice, its impact on human brain development remains unknown. We investigated the brain morphological characteristics of children with NBCCS. We evaluated brain T1‐weighted images from nine children with NBCCS and 15 age‐matched normal control (NC) children (mean [standard deviation], 12.2 [2.8] vs. 11.6 [2.3] years old). The diameters of the cerebrum, corpus callosum, and brain stem and the cerebellar volume were compared using two‐tailed t ‐tests with Welch's correction. The transverse diameters (150.4 [9.9] vs. 136.0 [5.5] mm, P = 0.002) and longitudinal diameters (165.4 [8.0] vs. 151.3 [8.7] mm, P = 0.0007) of the cerebrum, cross‐sectional area of the cerebellar vermis (18.7 [2.6] vs. 11.8 [1.7] cm 2, P = 0.0001), and total volume of the cerebellar hemispheres (185.1 [13.0] vs. 131.9 [10.4] cm 3, P = 0.0001) were significantly larger in the children with NBCCS than in NC children. Thinning of the corpus callosum and ventricular enlargement were also confirmed in children with NBCCS. We demonstrate that, on examination of the brain morphology, an increase in the size of the cerebrum, cerebellum, and cerebral ventricles is revealed in children with NBCCS compared to NC children. This suggests that constitutively active hedgehog signaling affects human brain morphology and the PI3K/AKT and RAS/MAPK pathways.